(untitled) (Cultura Económica, 2021)
This article begins by giving a general snapshot of the modern tendency to see regular laws in economic behavior and to displace the social in favor of the individual. In view of that, it searches Adam Smith’s thought for some clues to recover an idea of nature that is not absolute and an intermittent appeal to the need to take political measures when necessary, even if they oppose natural designs. For this, three of Smith’s central categories are described, together with some sayings of John Locke about the property and a description of the Great Fire that struck London in 1666 (as well as the genesis of the fire brigades). With all of the above in mind, it will seek to shed light on some less-attended aspects of the intersection between State, market and national life in Smithian work.